Implementing the Anti-Corruption Education Curriculum in State Islamic Senior High Schools (Madrasah Aliyah) in East Java - Munawir, Munawir; Thohar, Syafruddin Faisal (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2025)
Anti-corruption education is a crucial component in shaping a young generation with integrity and strong moral character. This study aims to analyze the models of curriculum insertion for anti-corruption education implemented in three state Islamic senior high schools (Madrasah Aliyah Negeri) in East Java: MAN 2 Malang, MAN Kota Surabaya, and MAN Model Bojonegoro. The main focus is to identify three models of curriculum insertion applied in these schools: integration into subjects, extracurricular activities, and the school environment. A qualitative approach with descriptive analysis was used to explore and compare the implementation of these models across the three institutions. The findings reveal that each school adopts a different approach to integrating anti-corruption education. MAN Kota Surabaya limits its efforts to subject-based insertion, emphasizing the teaching of anti-corruption values within specific lessons. MAN 2 Malang combines subject-based insertion with efforts to foster a school environment that supports integrity. Meanwhile, MAN Model Bojonegoro employs all three models simultaneously, aiming for a more holistic approach to character development. Despite their varying strategies, all three schools face similar challenges: limited teacher training and professional development, a lack of seminars and outreach on how to integrate anti-corruption values into religious education, and constraints in resources and facilities that affect the overall effectiveness of the curriculum.